PENDAMPINGAN DIGITALISASI UMKM DESA PELAGA - Hartini, Ni Made; Dewi, Tiara Kusuma (Synergy and Society Service, 2024)
The community service activities carried out in 2023 provide positive and useful value. This activity aims to provide assistance in the field of digital marketing to the Micro, Small and Medium Enterprises (MSME) community in Banjar Tiyingan, Pelaga Village. This aims to help MSMEs increase their online presence by creating online shops on the Shopee and Tokopedia marketplaces. Implementation time for MSME coaching will be carried out on February 8 2023 at the village office. The implementation duration of one week provides enough time for participants to learn and apply the skills they learn. Materials taught: Participants are given material regarding product photography techniques, product videos, creating business logos, as well as opening and managing online stores on Shopee and Tokopedia. This is a very relevant skill in online marketing. Participants: There were 30 participants who took part in this activity. They are business actors who already have micro and medium scale businesses. This shows that this activity is focused on communities that may need help in developing their online presence. The attendance rate of participants reached 90%, which shows a good level of participation in this activity. This indicates that participants have high interest and enthusiasm in learning digital marketing skills. Apart from direct meetings, participants can also study material offline or online from recordings that have been made. This provides flexibility for participants to study according to their own schedule.